Gastrodin Alleviates Oxidative Stress-Induced Apoptosis and Cellular Dysfunction in Human Umbilical Vein Endothelial Cells via the Nuclear Factor-Erythroid 2-Related Factor 2/Heme Oxygenase-1 Pathway and Accelerates Wound Healing In Vivo - Jialiang Lin; Jialiang Lin; Jialiang Lin; Yifeng Shi; Yifeng Shi; Yifeng Shi; Jiansen Miao; Yuhao Wu; Hao Lin; Jianwei Wu; Weimin Zeng; Fangzhou Qi; et al. (Frontiers Media S.A., 2019)
Aims: To explore the effect and mechanism of gastrodin (GAS) on human umbilical vein endothelial cells (HUVECs) apoptosis induced by oxidative stress and its function in wound healing.Main methods: HUVECs were incubated with tert-butyl hydroperoxide (TBHP) to induce endothelial cell dysfunction and GAS was used as a protector. Cell viability was detected by Counting Kit-8 (CCK-8). HUVECs apoptosis was evaluated by TUNEL assay and western blotting for cleaved caspase3 (C-caspase3) and other apoptosis-related proteins. Transwell migration assay, tube formation assay, and cell-matrix adhesion assay were performed to evaluated cell function of HUVECs. Transfection with nuclear factor-erythroid 2-related factor 2 (Nrf2) small interfering ribonucleic acid and western blotting for Nrf2, HO-1, and apoptosis-related proteins were performed to prove that Nrf2/HO-1 pathway is involved in the protective effects of GAS. The skin wound model of rat was used to assess the protective effects of GAS in vivo.Key Findings: The results show that treating HUVECs with GAS attenuated TBHP-induced apoptosis and cellular dysfunction, including cellular tube formation, migration, and adhesion. Mechanistically, we found that GAS protects HUVECs from TBHP-induced cellular apoptosis by activating the nuclear factor (erythroid-derived 2)-like 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway. An in vivo study illustrated that the oral administration of GAS enhances vascularization in regenerated tissue and facilitates wound healing.Significance: The findings of this study demonstrated that GAS may serve as a potential agent that accelerates wound healing.